2018
DOI: 10.1590/1807-3107bor-2018.vol32.0025
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of alcohol-containing mouthwashes on human enamel and restorative materials

Abstract: The objective of this study was to evaluate the in vitro effects, including surface morphological characteristics and chemical elemental properties, of different mouthwash formulations on enamel and dental restorative materials, simulating up to 6 months of daily use. Human enamel samples, hydroxyapatite, composite resin, and ceramic surfaces were exposed to 3 different mouthwashes according to label directions - Listerine® Cool Mint®, Listerine® Total Care, and Listerine® Whitening - versus control (hydroalco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 24 publications
2
33
0
1
Order By: Relevance
“…By observing the samples' mean values of ΔE, it was verified that the LW group showed the highest color variation and differed from the other groups subjected to immersion in mouth rinses as well as from the control group, which did not present a clinically significant change (ΔE < 3.7) [7,20]; but the groups treated with other mouth rinses also presented significant color variation similar to one another and different than the LW and CG groups. This result corroborates previous studies [2,8] and the results obtained by Torres et al [4], which demonstrated color changes promoted in tooth enamel by Listerine Whitening and Colgate Plax Whitening similar to conventional bleaching with 10% carbamide peroxide gel. This effect can be explained by time of use, although these agents have low hydrogen peroxide concentration and were used for a long period of time (12 weeks).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…By observing the samples' mean values of ΔE, it was verified that the LW group showed the highest color variation and differed from the other groups subjected to immersion in mouth rinses as well as from the control group, which did not present a clinically significant change (ΔE < 3.7) [7,20]; but the groups treated with other mouth rinses also presented significant color variation similar to one another and different than the LW and CG groups. This result corroborates previous studies [2,8] and the results obtained by Torres et al [4], which demonstrated color changes promoted in tooth enamel by Listerine Whitening and Colgate Plax Whitening similar to conventional bleaching with 10% carbamide peroxide gel. This effect can be explained by time of use, although these agents have low hydrogen peroxide concentration and were used for a long period of time (12 weeks).…”
Section: Discussionsupporting
confidence: 93%
“…However, in an in vitro study, Pelino et al [8], contrary to the findings of the present study, found no changes in tooth enamel structure after the use of different mouth rinses simulating the application for 90 and 180 days, using daily cycles 30 or 60 min, respectively; however, when simulating a long period of daily application with different cycles of immersion times and intervals, the study did not comply with the protocol of daily clini-cal use regarding brushing, immersion time, interval, and total period of treatment as indicated by the manufacturers and adhered to in the present study. This may produce different results than what occurs clinically since brushing one's teeth with fluoride toothpaste prior to or after immersion in the mouth rinses, as indicated by the manufacturers and performed in the present study, may result in changes in the enamel surface not detected in Pelino et al's study [8].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Several studies have reported that acidic solutions, including cola, orange juice, red wine, coffee, and gastric acid, can change the optical properties and surface roughness of toothcoloured dental restorative materials (10)(11)(12)(13)(14)(15). In addition, several oral hygiene solutions currently on the market can also affect the colour of dental restoration materials (16)(17)(18). Indeed, several brands of mouthwashes have a blue or green colour, which apparently is added to make them more visually appealing.…”
mentioning
confidence: 99%